Data: Two-phase Gas-Liquid Flow Regimes Identification in an S-shape Pipeline-Riser Using Doppler Ultrasonic Sensor - Nnabuife, Somtochukwu Godfrey; Whidborne, James F.; Lao, Liyun (Cranfield University, 2023)
Different flow regime data was generated experimentally at Cranfield University using a 2-inch multi-phase flow S-shape pipeline-riser test loop. In order to obtain the desired flow regime condition, the air-water flow rate was automatically regulated using the DeltaV system. Allfiles.Mat contains all the Air (Sm3/hr) - Water (Kg/s) flow regime conditions investigated. The data was recorded using the LabVIEW program but converted to a MATLAB file for easy access. All the flow conditions that fall under category 1 are in slugging condition, all that fall into category 2 are in bubbly condition, the ones that fall under category 3 are in churn flow condition and the ones that fall under category 4 are in annular flow condition. Data_wave2.mat is also a MATLAB file that contains all the flow conditions investigated. It contains the same data as in Allfiles.mat. You can use either Data_wave2.mat or Allfiles.mat files.
Keywords: 'Flow Regime Identification Methods'; 'Engineering Instrumentation'; 'Engineering Practice'